Product Promotion with Digital Marketing as a Marketing Strategy for UMKM ChaCha Kitchen, Blitar City - Riska Faulia Rahma; Rusdi Hidayat Nugroho (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Community Service through the KKN-T program aims to help develop the UMKM ChaCha Kitchen in Karangsari Village, Sukorejo District, Blitar City. The problem that occurs with UMKM ChaCha Kitchen is a lack of understanding in promoting their products with digital marketing. The method used is by identifying problems, assisting product promotions with digital marketing as a marketing strategy, and organizing socialization related to digital marketing. The results of this activity are in the form of creating content on ChaCha Kitchen's Instagram social media account, creating a website as a marketing support, and teaching product photos for content needs. The website contains information related to the business profile and products of UMKM ChaCha Kitchen. Product promotion with digital marketing as a marketing strategy for UMKM ChaCha Kitchen is able to improve the quality of content publication so that it can increase product sales.